REYE-LIKE SYNDROME IN THREE-YEAR-OLD CHILD - S. S. Postnikov; S. V. Mikhailova; G. P. Bryusov; M. N. Kostyleva; A. N. Gratsianskaya; A. E. Ermilin (Безопасность и риск фармакотерапии, 2018)
The article reviews the literature on classical and atypical Reye’s syndrome, explores the circumstances that contribute to its  occurrence, provides criteria for diagnosing with an illustration in the form of an authentic case of Reye-like disease in a child of 3 years  old. Reye’s syndrome is a disease manifested by acute  encephalopathy in combination with fatty degeneration of the  internal organs, mainly the liver. This condition was first described in  1963 by an Australian pathologist who identified 21 cases of the  disease in children with influenza A who were taking acetylsalicylic  acid, 17 children died. In the future, the circle of infections that  preceded the development of Reye’s syndrome-acute respiratory  infections, chickenpox, entero- and rotavirus infections, in rare  cases, hepatitis A and HIV, bacterial infections: mycoplasma,  chlamydia, whooping cough, shigella, salmonella. Drugs that can cause the development of this syndrome: tetracycline,  zidovudine, diclofenac sodium, mefenamic acid, paracetamol,  amiodarone, warfarin, phenothiazine derivatives, histaminolytics  (dimedrol), valproic acid. Along with drugs, insecticides, herbicides,  hepatotoxic fungi can be used as triggers of the syndrome. There is  an age dependence of the development of this syndrome. The  pathogenesis of classic Reye’s syndrome is associated with  generalized damage to the mitochondria primarily in the brain, as well as in the liver, kidneys, muscles, myocardium and pancreas,  with the disturbance of oxidation of fatty acids in them and the  formation of fat degeneration of varying degrees. In addition to the  classic Reye’s syndrome, atypical Reye’s syndrome or Reye-like  disease is isolated, occurs in children under 5 with congenital  disturbance of oxidation of fatty acids. We observed in our clinic the  case of Reye-like disease in a girl of three years with infection and  taking antipyretics. In the discussion section, the features of the  given case are noted, the question of the appropriateness (in view of the generality of the clinic and the mechanisms of development) of  dividing the syndrome into classical and atypical is discussed. A new  name for both conditions is proposed — Reye’s disease in honor of  the discoverer, highlighting its two forms with an early and late  onset. Given the morphological changes in this syndrome —  steatosis of internal organs — authors seem to be appropriate  measures aimed at treating secondary mitochondrial insufficiency  and fatty dystrophy.